ANALISIS ANALYSIS OF AFFIXATION ERRORS ON THE ONLINE NEWS PORTAL LANGGAM.ID: ANALISIS KESALAHAN AFIKSASI PADA PORTAL BERITA ONLINE LANGGAM.ID - Mia Amelia Artati; Yulia Sri Hartati; Ria Satini (Jurnal Kata, 2024)
Through the affixation process, it can be seen how the grammatical process of a basic word or basic form is. The aim of this research is to describe the forms of affixation errors, namely prefixes, infixes, suffixes, confixes on the online news portal langgam.id. This type of research is qualitative research with descriptive methods. The data source for this research is the online news portal langgam.id. Data obtained from online news langgam.id. The data collection technique used was the free-to-read, involved listening method using note-taking techniques.The data validation technique is the data triangulation technique, namely the theory and investigator triangulation technique. The data analysis technique used in this research used the intralingual matching method. Based on the results of research carried out on the online news portal langgam.id, it turns out that there are still errors in the language of the affixation process, namely prefixes and confixes. The results show that there is an error in the affixation process in the langgam.id online news which is taken from several news stories as data sources. The most common errors found are errors in the confix affixation process, namely confix errors that are written incorrectly according to the applicable language rules.